2010
DOI: 10.1002/hep.23744
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Sustained Virological Responders With Histologically Advanced Chronic Hepatitis C†,‡,§,¶

Abstract: Retrospective studies suggest that subjects with chronic hepatitis C and advanced fibrosis who achieve a sustained virological response (SVR) have a lower risk of hepatic decompensation and hepatocellular carcinoma (HCC). In this prospective analysis, we compared the rate of death from any cause or liver transplantation, and of liver-related morbidity and mortality, after antiviral therapy among patients who achieved SVR, virologic nonresponders (NR), and those with initial viral clearance but subsequent break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
355
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(377 citation statements)
references
References 16 publications
13
355
1
8
Order By: Relevance
“…In chronic hepatitis, HCC occurrence clearly depends on continued presence of hepatitis viruses and chronic inflammation. In contrast, patients with cirrhosis have relatively low but real risks of HCC occurrence and hepatic decompensation despite SVR [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In chronic hepatitis, HCC occurrence clearly depends on continued presence of hepatitis viruses and chronic inflammation. In contrast, patients with cirrhosis have relatively low but real risks of HCC occurrence and hepatic decompensation despite SVR [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and a meta-analysis have concluded that eradication of HCV with antiviral therapy reduces the risk of HCC in patients with chronic hepatitis C, independent of fibrosis stage [79,80]. However, a reduction in the risk of HCC does not necessarily indicate improvement in overall survival, and interferon is less effective in patients with cirrhosis.…”
Section: Antiviral Therapy and Effect On Incidence Of Hepatocellular mentioning
confidence: 99%
“…While up to 80% of the genotype 2 and 3 infected and 40-50% in genotype 1 patients can be cured, the response rate of genotype 4 in many clinical repots is showing SVR rates exceeding 60% 14 . Once achieved, an SVR is associated with long-term clearance of HCV infection, which is regarded as a virologic ''cure,'' as well as with improved morbidity and mortality 18 .…”
Section: Introductionmentioning
confidence: 99%